Testing the Fire Resistance of Fiberglass Composite Material with a Mixture of Green Mussel Shell Waste - Paska, Adhi; Yusrizal, Yusrizal; Hermawan, Maman; Soeboer, Deni Achmad (Journal La Lifesci, 2025)
This study aims to evaluate the effect of adding green mussel shell powder (CKH) on the fire resistance of Fiberglass composite materials used in fishing vessel hulls under 5 GT. The composite was made using the hand lay-up method with variations in CKH composition of 0%, 10%, 20%, 30%, 40%, and 50%. Testing was carried out using the ASTM D635 standard to determine the burning rate. Statistical analysis using logistic regression to determine the linear relationship between variables. Statistically, logistic regression states a p-value <0.05 and is suitable as a reference model to determine the value of CKH powder composition with the burning rate of the material. This study shows that specimens with the addition of 20% CKH increase fire resistance by 8.56% (13.10 mm/min), while the addition of 50% CKH increases up to 19.92% (11.47 mm/min). So that the more CKH composition additions can increase the fire resistance of the material. These results indicate that CKH waste has the potential as an environmentally friendly additive that improves ship safety.